2016
DOI: 10.1016/j.postcomstud.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in political trust: Comparing the Vysocina and Usti Regions

Abstract: This article deals with the factors influencing the degree of trust in political institutions at three levels of government in the Czech Republic (national, regional and local) in two dissimilar regions in the time of economic crisis in 2009, the year when citizens of the Czech Republic experienced the negative impacts of growing unemployment and a substantial decline in real GDP. Two competitive theories - the cultural and the performance explanation - were used as a theoretical framework. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Second, this study also adds to the emerging empirical evidence on how contextual factors influence the criteria citizens use to develop institutional trust (e.g., Hakhverdian & Mayne ; Čermák et al. ). Neundorf (), for instance, showed that having lived under socialist rule impacts the drivers of institutional trust.…”
Section: Discussionmentioning
confidence: 84%
“…Second, this study also adds to the emerging empirical evidence on how contextual factors influence the criteria citizens use to develop institutional trust (e.g., Hakhverdian & Mayne ; Čermák et al. ). Neundorf (), for instance, showed that having lived under socialist rule impacts the drivers of institutional trust.…”
Section: Discussionmentioning
confidence: 84%
“…Obce jsou základními územními samosprávnými celky a obecní samospráva a starostové a starostky 1 jako její představitelé se dlouhodobě těší nejvyšší důvěře obyvatel [CVVM 2017;Čermák, Stachová 2010;Čermák, Mikešová, Stachová 2016]. Přístupy k vedení obcí v Česku se však významně liší a jsou ovlivněny mnoha faktory, což se následně promítá i do fungování obcí.…”
Section: úVodunclassified
“…Then, there are cross-sectional studies which focus specifically on trust in government (i.e., in the political executive body -the cabinet) and investigate its various determinants (Čermák et al, 2016;Christensen & Laegreid, 2005;Christensen et al, 2020;Holmberg et al, 2017;Miller, 2004;Muñoz, 2017;Ken Newton, 2006;Nye et al, 1997;Torcal, 2014;van de Walle & Bouckaert, 2003;Wilkes, 2015). They demonstrate that trust in government is closely related to the evaluations of its performance, perceptions of responsiveness, etc.…”
Section: Research Gaps: Trust In Government As Generalized Vs Specifi...mentioning
confidence: 99%
“…This does not change the overall interpretation of the results, which focuses on relative correlations strengths, i.e., investigating whether they vary between indicators and levels of governance (as their variation would indicate differentiation in political trust across levels of governance against the backdrop of changing socio-political and economic conditions). 35 National government is responsible for basic entitlements like unemployment benefits, old-age pensions and incapacity allowances; previous studies have shown that unemployment has implications for trust in national government (Čermák et al, 2016;Dolan et al, 2009;Halvorsen, 2016;Muro & Vidal, 2017;van Erkel & van der Meer, 2016). Subnational governments, on the other hand, need to deal with social consequences of unemployment, such as eroding local capital, demand for social housing or rising crime (Sellers & Lildström, 2007).…”
Section: Trust Trends and Macro-economic Conditions: Comparative Evid...mentioning
confidence: 99%